The specific features of the effect of excitation intensity and concentration on the population of the triplet level of molecules in glassy matrices at 77 K - Mihail Ivanovich Deryabin; Marina Vasilyevna Erina; Natalya Vladimirovna Zhdanova (Наука. Инновации. Технологии)
The effect of the concentration and parameters of the sample on the intensity of phosphorescence of glassy solutions of organic compounds with high concentration has been studied. The results obtained under uniform distribution of the intensity of the exciting light in the sample have been compared with them taking into account decrease of the intensity by absorption of light during its propagation along the sample. It is shown that dependence of the intensity of phosphorescence on concentration becomes nonlinear and tends to saturation as consequence of attenuation of the exciting light under it absorption. This effect was demonstrated in a glassy solution of benzophenone in toluene in the range of concentrations from 0.05 to 0.5 mol/l and thickness of the sample 4 mm.